2003
DOI: 10.1115/1.1523065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Some Existing Correlations to Predict Head Degradation of Centrifugal Slurry Pumps

Abstract: In order to optimally design a slurry transportation system, it is necessary to know how the presence of solids will change the performance of the slurry pump to be installed. This paper makes the comparison of some existing correlations available in the literature to predict the head reduction factors of such centrifugal pumps handling slurries. For this purpose, a large number of published data for various centrifugal slurry pump tests in the literature have been used to develop a new correlation and then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…Egin and Gur etc al 6 have evaluated some existing correlations to predict head degradation of centrifugal slurry pumps. A new correlation has been developed in order to predict head reductions of centrifugal pumps when handling slurries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Egin and Gur etc al 6 have evaluated some existing correlations to predict head degradation of centrifugal slurry pumps. A new correlation has been developed in order to predict head reductions of centrifugal pumps when handling slurries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is generally accepted that both K H and K h are basically a function of concentration of solids (C W or C V ), specific gravity of solids (S), and representative diameter of particles d W in the pumped slurry [8,10,13,20]. A relatively recent paper by the present author indicated that the head reduction factor (K H ) could be better correlated with the ratio of the representative diameter of particle (d W ) to the outer diameter of the pump impeller (d 2 ) [13]. However, in this study, it was observed that the inclusion of impeller diameter into the analysis of efficiency reduction factor (K h ) could not provide accurate predictions.…”
Section: Derivation Of the Proposed Correlationmentioning
confidence: 99%
“…Based on the procedure described briefly above, a Cþþ-based computer code has been written and all training tests have been performed on a personal computer. Before running the code, both input and output parameters were normalized within the (0.1 -0.9) range using P n ¼ 0:1 þ 0:8 P À P max P max À P min (13) where P n is the unified value of the corresponding parameter P, P max and P min denote the maximum and minimum values of parameter P, respectively. In order to compare the predicted values for different network parameters (such as learning rate, momentum coefficient, and the number of hidden units) and the desired values, the mean relative error defined by the following relation…”
Section: Neural Network and Its Application For K Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In [46] a correlation was derived from the test data reported by various authors (in total 850 measuring points). Here, the head impairment is proportional to the mass concentration x, Eq.…”
mentioning
confidence: 99%